The impact of misinformation on the COVID-19 pandemic - Maria Mercedes Ferreira Caceres; Juan Pablo Sosa; Jannel A Lawrence; Cristina Sestacovschi; Atiyah Tidd-Johnson; Muhammad Haseeb UI Rasool; Vinay Kumar Gadamidi; Saleha Ozair; Krunal Pandav; Claudia Cuevas-Lou; Matthew Parrish; Ivan Rodriguez; et al. (AIMS Press, 2022)
Since the inception of the current pandemic, COVID-19 related misinformation has played a role in defaulting control of the situation. It has become evident that the internet, social media, and other communication outlets with readily available data have contributed to the dissemination and availability of misleading information. It has perpetuated beliefs that led to vaccine avoidance, mask refusal, and utilization of medications with insignificant scientific data, ultimately contributing to increased morbidity. Undoubtedly, misinformation has become a challenge and a burden to individual health, public health, and governments globally. Our review article aims at providing an overview and summary regarding the role of media, other information outlets, and their impact on the pandemic. The goal of this article is to increase awareness of the negative impact of misinformation on the pandemic. In addition, we discuss a few recommendations that could aid in decreasing this burden, as preventing the conception and dissemination of misinformation is essential.